The social world of elite youth football in Germany - crisis, reinvention, optimization strategies, and the role of schools - Naglo, K. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
The objective of this article is to analyse the system of top-flight youth football in Germany, its main institutions - the Academies (Nachwuchsleistungszentren) and the Elite Schools of Football (Eliteschulen des Fußballs) - and the relationship between them. The analytical focus centres on examining the ways in which quasi-professional youth football and the German educational system have cooperated in recent years. Special emphasis will be placed on the reconstruction and professionalization processes in the context of a perceived crisis in German football generally dating from the late twentieth century. It will be argued that the idea of crisis appears to be of systemic value for the social world of football in Germany. In the world of football, constant reference to crisis helps to create shared meaning among and between groups whose interests do not necessarily coincide, lending support to the argument that the idea of a crisis is important in facilitating action and change. The analysis will be underpinned by a case study focusing on the youth section of German Bundesliga club FSV Mainz 05 and one of its partner schools. Different perspectives on cooperation will be explored with a focus on the various perspectives of actors involved, drawing especially on qualitative and ethnographic interviews and fieldwork carried out in 2018 and 2019.